Pengaruh Laba Akuntansi, Total Arus Kas, Net Profit Margin, Dan Tingkat Laverage Terhadap Return Saham Perusahaan Asuransi Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2015-2020 - Tina Novianti Sitanggang; Hendrico Sipahutar; Tina Hastarina Wau (Journal of Economic, Bussines and Accounting (COSTING), 2022)
The assessment is aimed at analyzing how much influence the Accounting Profit, Total Cash Flow, NPM, and Laverage Level on Stock Returns in Insurance Companies. In this study the population used is one of the Insurance Companies Liste on the IDX in 2015-2020. This type of study is a quantitative descriptive study using secondary data. In this study using 66 research samples, but due to outliers the data became 54 research samples. The data analysis technique used in this study is multiple linear analysis, the coefficient of determination test and hypothesis testing using t test and f test. The results of this studyshow that simultaneously Accounting Profit, Total Cash Flow, NPM, and Laverage Level do not have a substansial impact on the stock return of insurance companies listed on the IDX in 2015-2020. While partially Accounting Profit have a positive ang significant effect on Stock Ruturn, while Total Cas Flow, NPM, and Leverage Levels have no effect on Stock Return of Insurance Companies Listed on the IDX 2015-2020. Key words : Laba Akuntansi, Total Arus Kas, Net Profit Margin, dan Laverage.